Two New Cholic Acid Derivatives from the Marine Ascidian-Associated Bacterium Hasllibacter halocynthiae - Kim, Sung Hun; Shin, Yun Kyung; Sohn, Young Chang; Kwon, Hak Cheol (MDPI AG, 2012)
The investigation of secondary metabolites in liquid cultures of a recently discovered marine bacterium, Hasllibacter halocynthiae strain KME 002(T), led to the isolation of two new cholic acid derivatives. The structures of these compounds were determined to be 3,3,12-trihydroxy-7-ketocholanic acid (1) and 3,3,12-trihydroxy-7-deoxycholanic acid (2) through HRFABMS and NMR data analyses.
Keywords: BILE-ACIDS; SP NOV.; ROSEOBACTER CLADE; RORETZI; ANTIBACTERIAL; ALKENES